Investigating Pre-Service English Teacher in Using Language in the Classroom - Muhammad Reza Pahlevi; Iwan Ridwan (ENGLISH EDUCATION DEPARTMENT - UNIVERSITAS SINGAPERBANGSA KARAWANG, 2018)
This study aims at investigating the ways Pre-service English Teacher (PET) uses English in the classroom. Observation data described how PET used English in one of Junior High School in Karawang. The results showed there were three findings emerged. Firstly, the use of English was practiced in stimulating students at the pre-lesson stage. Secondly, the PET tended to use Indonesian in main lesson. Finally, in the post-lesson stage English was used more dominantly but Indonesian is more dominant in the reflection stage.